Depression in the Elderly. Consensus Statement of the Spanish Psychogeriatric Association - Agüera-Ortiz, Luis; Claver-Martín, María Dolores; Franco-Fernández, María Dolores; López-Álvarez, Jorge; Martín-Carrasco, Manuel; Ramos-García, María Isabel; Sánchez-Pérez, Manuel (Frontiers in Psychiatry, 2020)
Introduction. Despite its high frequency and impact, present knowledge about depression in the elderly is still scarce and often controversial. This article reports the results and most relevant conclusions of a Delphi-based consensus on geriatric depression promoted by the Spanish Psychogeriatric Association. Methods. A 78-item questionnaire was developed by 7 highly specialized geriatric psychiatrists and was evaluated using the Modified Delphi technique in two rounds answered by 35 psychiatrists with an extensive expertise in geriatric depression. The topics and number of questions (in brackets) covered were: Concepts, clinical aspects and risk factors (12); Screening and diagnosis (7); Psychotic depression (17); Depression and dementia (5); Antidepressant drug treatment (18); Non-pharmacological biological treatments (5); Psychotherapeutic treatments (4); Comorbidity and preventive aspects (6); Professional training needed (4) Alongside the Delphi study, the expert panel’s opinion on the antidepressants of choice in 21 common comorbid conditions and on different strategies to approach treatment-resistant cases in terms of both efficacy and safety was also assessed. Results. After the two rounds of the Delphi process, consensus was reached for 59 (75.6%) of the 78 items. Detailed recommendations are included in the text. In terms of pharmacological treatments, agomelatine was the most widely mentioned drug to be recommended in comorbid conditions in terms of safety. Desvenlafaxine, sertraline, and vortioxetine, were the most frequently recommended antidepressants in comorbid conditions in general. Combining parameters of efficacy and safety, experts recommended the following steps to address cases of treatment resistance: 1. Escalation to the maximum tolerated dose; 2. Change of antidepressant; 3. Combination with another antidepressant; 4. Potentiation with an antipsychotic or with lamotrigine; 5. Potentiation with lithium; 6. Potentiation with dopamine agonists or methylphenidate Discussion and conclusions. Consensus was reached for a high number of items as well as for the management of depression in the context of comorbid conditions and in resistant cases. In the current absence of sufficient evidence-based information, our results can be used to inform doctors about clinical recommendations that might reduce uncertainty in the diagnosis and treatment of elderly patients with depressive disorders.